Corporate social responsibility, green financial system guidelines, and cost of debt financing: Evidence from pollution‐intensive industries in China. (30th November 2021) - Li, Yuanhui; Chen, Rongrong; Xiang, Erwei
Abstract: Using a sample of publicly listed firms from 2014 to 2019 in pollution‐intensive industries in China, this study investigates the effect of corporate social responsibility (CSR) on corporate cost of debt financing and how the issuance of the "Green Financial System Guidelines" moderates the above relationship. We find that high CSR performance (including responsibility for shareholders, employees, suppliers and customers, the environment, and the community) is associated with low cost of debt in polluting companies. Moreover, the "Green Financial System Guidelines" strengthens the role of CSR in reducing corporate cost of debt. Further analyses reveal that CSR reduces cost of debt by reducing information asymmetry and business risk, and that green credit development strengthens the role of CSR in reducing corporate cost of debt. Our baseline results are robust to alternative measures and tests that address potential endogeneity concerns by employing the Heckman two‐stage and propensity score matching (PSM) methods.